Проблема становлення артпедагогіки як інноваційної технології в країнах Європи та США - Алексінцева, Тетяна; Aleksintseva, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті здійснений огляд наукових досліджень із проблематики артпедагогіки у країнах Східної та Західної Європи та США. Охарактеризовано процес становлення та розвитку артпедагогіки як самостійної педагогічної галузі, інноваційної педагогічної технології. Окреслено тенденції впровадження методів артпедагогіки у вищі навчальні заклади. Зроблено висновок про перспективи розвитку артпедагогіки в українському освітньому просторі. In the article, a review of scientific researches in the area of art pedagogics in the countries of Eastern and Western Europe and the USA is carried out. Basic tendencies of this newest pedagogical technology are determined, namely: in the countries of Western Europe and the USA it is mainly a use of art therapy at schools to form a healthy and socially productive personality, who is able to solve problems, get along with stress, as well as to develop communicative skills and healthy necessities of children and young people; in the East European countries as the mean of comprehension of issues of the day, development of self-examination abilities and successful social adaptation. Deep interest to art pedagogics as independent pedagogical industry and innovative pedagogical technology is marked in Russia. There is a great variety of research works of the Russian scientists, and the methods of art pedagogics are introduced into all educational levels - from preschool to high school. The short review of the development of art pedagogics in Ukraine is carried out. The conclusion about the prospects of art pedagogics in Ukrainian educational space is drawn, as the application of methods of art pedagogics opens new possibilities in modern pedagogics, promotes interest to the capture of knowledge, forms new abilities and skills, assists in active development of psychical processes and properties of children and young people, first of all, creativity, independence, skills of self-expression and self-reflection, and consequently, ability to adapt oneself to a macrosocial environment.
The Problem of the Formation of Art Pedagogics as an Innovative Technology in Europe and the USA
Keywords: артпедагогіка; арт-терапія; інноваційна педагогічна технологія; мистецтво; art pedagogics; art therapy; innovative pedagogical technology; art